PENGGUNAAN MEDIA PADDING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA PESERTA DIDIK KELAS V SEKOLAH DASAR - Abidatul Hilma, Agustin; Susetyo Rukmi, Asri; Nudiya Lissholati, Aminah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the improvement of student learning outcomes through the use of Padding media in Mathematics learning. This study uses the type of Collaborative Classroom Action Research (CCAR) which involves collaboration between researchers and related parties in schools and this study was carried out through two cycles. Each cycle consists of planning, implementation, observation and reflection. The subjects of the study were grade V students of SDN Lakarsantri II/473 Surabaya, with a total of 28 students. In data collection, researchers used tests, observations and documentation. The results of the study showed that the use of Padding media had a gradual increase in student learning outcomes, from 25% in the pre-cycle to 36% in cycle 1, and then increased again to 82% in cycle 2. Based on the results of the study, it can be concluded that the use of Padding media has proven effective in improving student learning outcomes. Thus, the application of Padding media can be used as an alternative strategy that can be applied by teachers to improve the quality of learning and achievement of student learning outcomes.